The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/pat.3287
|View full text |Cite
|
Sign up to set email alerts
|

Compressive char strength of thermoplastic polyurethane elastomer nanocomposites

Abstract: This research encompasses the study of testing protocols and the design of sensors for evaluating the compressive strength of the char layer of ablative material used in solid rocket motors (SRMs). The testing protocol that has been developed is the continuation of previous work for determining the compressive strengths between different SRM insulation materials. A crushing test method was further developed, and a sensor platform was assembled to perform the tests. The test procedure consists of measuring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…This protective carbonaceous char may act as a thermal barrier to prevent polymer degradation and also avoids the transfer of flammable gases to vapor phase and penetration of oxygen into condensed phases during combustion . Insulation character of char residue can be evaluated from its properties such as cohesion, morphology, thickness, and porosity . Therefore, the remaining carbonaceous residues after cone calorimeter tests were investigated using XRD and Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protective carbonaceous char may act as a thermal barrier to prevent polymer degradation and also avoids the transfer of flammable gases to vapor phase and penetration of oxygen into condensed phases during combustion . Insulation character of char residue can be evaluated from its properties such as cohesion, morphology, thickness, and porosity . Therefore, the remaining carbonaceous residues after cone calorimeter tests were investigated using XRD and Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…45 Insulation character of char residue can be evaluated from its properties such as cohesion, morphology, thickness, and porosity. 46,47 Therefore, the remaining carbonaceous residues after cone calorimeter tests were investigated using XRD and Raman spectroscopy. Figure 11A).…”
Section: Characterization Of the Residual Charmentioning
confidence: 99%
“…Lee et al studied the ablative properties of TPU elastomer with different nano reinforcements and concluded that multiwalled CNT composite is a good choice of ablative reinforcement, whereas carbon nanofiber is not an ideal ablative material. Jaramillo et al put an effort to optimize the formulation of TPU as an EHSM in an SRM along with other EHSMs.…”
Section: A Focus On Ehsms For Srmmentioning
confidence: 99%
“…Jaramillo et al . developed a compressive char strength to evaluate thermoplastic polyurethane elastomer nanocomposites . Because of its creation, the corrected testing apparatus has served as a novel method for evaluating the properties of char and was once again called upon for this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…This study involves the use of a previously built compressive strength sensor and shear strength sensor at UT Austin. A picture of the shear sensor and a sketch of the shear sensor's set up is presented in Fig.…”
Section: Introductionmentioning
confidence: 99%